Clinical Competence and Self-Efficacy on Caring Behavior with Work Attachment as an Intervening Variable - K Saleky, Maria Suzzana (Lembaga Penerbitan Universitas Esa Unggul, 2025)
This research is based on the results of initial observations which inform about an increase in patient safety incidents in 2023 compared to 2022. The aim of this research is to reveal empirically the influence of clinical competence and self-efficacy on caring behavior with work engagement as an intervening variable. This type of research is quantitative with a cross sectional study design. The population used was inpatient nurses. The sampling technique used non-probability, with calculations using the Slovin formula with an error rate of 5%, so that a sample size of 133 respondents was found. The data collection technique uses a questionnaire, and the analysis method uses three box method analysis and SEM. The results of the analysis prove that simultaneously and simultaneously clinical competence, self-efficacy and work engagement influence caring behavior. Clinical competence and self-efficacy influence work engagement. Work engagement intervenes in the relationship between clinical competence and self-efficacy on caring behavior.